2016
DOI: 10.1097/cin.0000000000000229
|View full text |Cite
|
Sign up to set email alerts
|

Nurses’ Use of a Web-Based National Guide for Child Health Care

Abstract: Rikshandboken i Barnhälsovård is a Swedish Web-based guide for child healthcare, providing quality-ensured guidelines and support contributing to equality in child healthcare among all children. In 2015, a new child healthcare program was implemented and made available in this Web-based guide. The aim of this study was to investigate how child healthcare nurses use Rikshandboken i Barnhälsovård and factors affecting its use. The study was a comprehensive Web survey of 2376 child healthcare nurses in Sweden ans… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
3
2

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(12 citation statements)
references
References 16 publications
1
11
0
Order By: Relevance
“…Participants' collective understanding of RHB as a resource for learning complies with earlier studies of CHC nurses' use of RHB 15,19 where access to research, pedagogical materials, instructional videos, discussion forums, and e-learning were suggested as improvements of RHB. According to the Swedish Society of Nursing, 7 CHC nurses should be able to educate individual and groups of parents, students, and colleagues.…”
Section: Discussionsupporting
confidence: 63%
See 4 more Smart Citations
“…Participants' collective understanding of RHB as a resource for learning complies with earlier studies of CHC nurses' use of RHB 15,19 where access to research, pedagogical materials, instructional videos, discussion forums, and e-learning were suggested as improvements of RHB. According to the Swedish Society of Nursing, 7 CHC nurses should be able to educate individual and groups of parents, students, and colleagues.…”
Section: Discussionsupporting
confidence: 63%
“…The result showed that the national CHC program is still not implemented in all county councils/regions, and the use of RHB varied. This was also found in earlier studies of Swedish CHC and RHB 15,16,19 and contradicts the intention to offer an equal CHC contributing to equality in child health. 14 An overall category of understanding was RHB as a contributing determinant to an equal CHC and national equivalence.…”
Section: Discussionmentioning
confidence: 55%
See 3 more Smart Citations